“Necesidad de reformar el art. 272 del código orgánico integral penal, en relación de establecer excepciones de responsabiliadd penal, en la existencia de nexos de parentesco entre el infractor y quien guarda silencio de la conducta delictiva o el ocultamiento”. - Chandi Zúñiga, Wilfrido Napoleón (2015)
The second paragraph of Article 272 provides in relevant part as regulates matters relating to COVER independent crime and sentencing 1 to 3 years states: "with same penalty shall be punished who know the criminal conduct of a person or persons, provide them accommodation or hiding, or provide them with the means to take advantage ... "among other things, instituting independently an offense the previous regulation did not contemplated, the aforementioned situation I consider appropriate because the concealing never participated in the commission of the offense, previous or simultaneous actions and harm could have a degree of intervention unwillingness to execute a criminal, to warrant a penalty as stated erroneously our Criminal Code. Now if we contrast the new legal concept already indicated, Article 44 of the old Penal Code, we find that is largely a verbatim copy of the previous regulation, with slight variations in certain terms that ultimately represents the same regulatory spirit does not change its nature. In the previous regulation under the heading of those responsible for the violations, exceptions to cover, among which consisted relative to spouses, their parents, children, siblings or affinity up to the second degree is established; with this exception instituting criminal liability protection indisputable benefit of the most basic and elementary family ties; is protected as it could not be otherwise the cell of society, in response to the natural reaction between parents and children and vice versa, seeking where possible to establish a degree of protection to self-protection would say between the closest members family; even a religious order mandate says we should honor father and mother. It is clear that with respect to the cover as a separate offense are not against this figure; but if we believe there is an error in the Penal Code of Integral by failing to establish as exceptions to criminal liability, the existence of kinship ties as indicated between the offender and who is silent in criminal conduct or concealment after execution of any penalty, in the terms established by the second paragraph of Article 272 of the new penal regulatory body; error that must be corrected for the benefit of family harmony.